Argumentationen über den Klimawandel in Schweizer Medien Entwicklung einer sektoralen Argumentationstheorie und -typologie für den Diskurs über Klimawandel zwischen 2007 und 2014 - Kammermann, Nadine (Sprache und Wissen (SuW), 2022)
This book establishes a typology of the arguments made about climate change in the German-speaking Swiss media between 2007 and 2014. By combining corpus linguistic, pragma-dialectical, and discourse analytical approaches, the sectoral theory of argumentation developed in this volume and embedded within its discourse-historical approach provides access to the material topoi of mass-media discourse about climate change.